FISHERY AND POPULATION DYNAMICS OF THE WINDOWPANE OYSTER, PLACENTA PLACENTA (LINNAEUS), FROM KAKINADA BAY - Narasimham, K A (Indian Journal of Fisheries, 2011)
The catch trends of the windowpane oyster at Yetimoga landing centre during 1978-81 are described. The instantaneous rates of mortality of Placenta placenta are estimated as Z = 4.0, M = 1.3 and F = 2.7. The life-span is 3.4 years. The study on the yield in weight per recruit shows that under the current ftof 0.89 year, the yield increases without reaching a maximum with increased F. It is also observed that maximum yield can be obtained at tc i= 0.8 which is close to the current value. It is recommended that the present tic and F can be maintained with advantage.